Unravelling the aptamer-analyte interaction dynamics through fluorescence quenching in graphene quantum dots (GQDS) based homogeneous assays - Ang, Wei Li (2021)
Graphene quantum dots (GQDs) are used here as a biosensing platform for the recognition of the major food contaminant ochratoxin A (OTA), with a fluorescently labelled DNA aptamer (FAM OTA aptamer) functioning as the biorecognition element. The detection principle lies in the formation of noncovalent interactions between the FAM OTA aptamer and the GQD surface, and the consequent fluorescence quenching. The further change in the fluorescence signal, induced by the formation of the FAM OTA Aptamer/OTA conjugate during the detection step, could then be correlated to the presence and concentration of the target analyte. Upon tuning the concentration of GQDs, a switch in the biorecognition mechanism occurred. Specifically, while a lower GQD concentration (0.060 mg/mL) resulted in a restoration of the fluorescence intensity upon incubation with OTA, a higher GQD concentration (0.150 mg/mL) provided a further quenching of the final fluorescence intensity. Upon further calibration study, it was discovered that the latter mechanism provided a better option in terms of linearity of response, detection limit and selectivity.